THE EFFECT OF COOPERATIVE LEARNING MODELS ON MATHEMATICS LEARNING OUTCOMES IN TERM OF STUDENT COOPERATION - Anang Arga Priambadha; Uswatun Khasanah (Universitas Ahmad Dahlan, 2019)
Mathematics learning in the seventh grade of SMP Negeri 3 Wates Kulon Progo regency for the academic year 2017/2018 made the students bored and less enthusiastic. The cooperation between students is not optimal. This study aims to determine whether or not there is a significant influence (1) the factors of cooperative learning model on the students 'mathematics learning outcomes, (2) factors of student learning between students' learning achievement, (3) the interaction between cooperative learning model and student-to-student cooperation learning mathematics students. (4) between ST-class and PBL-class learning of mathematics learning outcomes, (5) between ST and PBL type cooperative learning models of mathematics learning outcomes. This study population was all seventh-grade students of State Junior High School (SMP Negeri) 3 Wates Kulon Progo of the academic year 2017/2018, which consisted of four classes, namely class VII-A, VII-B, VII-C, VII-D and amounting to 138 students. The sample consists of two classes taken at random. Data analysis techniques used include prerequisite tests and hypothesis tests. The results of the study at a significant level of 5% with df = 1 showed no significant influence (1) factor model of cooperative learning on mathematics learning results, obtained Fobs (A) = 0,262 <F0,05; 1,65 = 3,989 (2) factors of student's co-work on mathematics learning result, obtained Fobs (B) = 0,270 <F0,05; 1,65 = 3,989 (3) the interaction between cooperative learning model and student's co-work on mathematics learning result, obtained by Fobs (AB) = 0,043 <F0,05; 1,65 = 3,989. (4) ST-type cooperative learning model has no more significant effect than PB-class student intercourse, it is obtained tcount = -12,574 <t0,05,67 = 1,996, with df = 67. (5) ST type cooperative learning model no more significant than the cooperative learning model of PBL type, obtained tcount = -0.828 <t0,05; 8 = 2.306, with df = 8.